Assessment of Landuse and Landcover Changes and its Implications to Flooding Along Omambala Flood Plain, Anambra State - Emmanuel, Agulue; Nnabuike, Okoye; Iheukwumere, Samuel Oji; Nkwocha, Kelechi Friday (International Journal of Geography and Geology, 2020)
This paper assessed the landuse and landcover changes and its implications to flooding along Omambala floodplain in Anambra State. The paper aimed at identifying the landuse and landcover types in Omambala floodplain in relations to their temporal dynamics, the extent of landuse change and its implication to recurring incidence of flood disaster in the study area over a period of 20 years starting from the year 1998 to 2018. Multi-temporal Landsat TM and ETM+ imageries were obtained at 10 years interval; 1998; 2008 and 2018 to observe the pattern of landuse and landcover along the floodplain over the period of study. Population data of study area were obtained from National Population Commission on four time paints as to understand the rate of land conversion and modification of the floodplain. Visual interpretation method was used to map landuse and landcover into five classes namely: waterbody; built-up; sparse vegetation; bare surface and dense vegetation. The result of the analysis of the imageries showed a considerable change in the pattern of landuse and landcover classes within the period under study. There was also a considerable population growth leading to progressive conversion of natural vegetation to other human activities with Built-up lands sparse vegetation and bare surface on the increase as well as their attendant consequences. However, the study concluded that various anthropogenic landuse activities especially poor farming system leading to increasing sparse vegetation, bare surface and built-up area are major factors that affects natural vegetation thereby worsening the incidence of flooding in the study area. The research therefore recommends relocation of settlements, greening of space already turning bare, effective floodplain management and continues monitoring of changes on land characters to ensure environmental sustainability and to forestall recurring incidence of flooding along the floodplain.